‘Effective Communication Strategies in Travel: experiential storytelling’ / In this module, the instructors illustrate effective communication strategies in travel and they refer to the changing nature of travel. However, this time, we do it by studying another means of communication that facilitates sharing of our travel experiences. This form of travel communication strategy is built around experiential storytelling. - Γαλατσοπούλου Φανή (ΑΡΙΣΤΟΤΕΛΕΙΟ ΠΑΝΕΠΙΣΤΗΜΙΟ ΘΕΣΣΑΛΟΝΙΚΗΣ, 2015)
In this module, the instructors illustrate effective communication strategies in travel and they refer to the changing nature of travel. However, this time, we do it by studying another means of communication that facilitates sharing of our travel experiences. This form of travel communication strategy is built around experiential storytelling.: Αυτό είναι το μόδουλ 11, ο οποίος ονομάζεται «Εφεκτικές Κοινωνικίες Στρατηγίες στον Προβλήμα», «Εξιπιστωτική Πραγματικότητα». Σε αυτό το μόδουλ, όπως και το προηγούμενο μόδουλ, εφαρμόζουμε Εφεκτικές Κοινωνικίες Στρατηγίες στον Προβλήμα, και αναφέρονται στην αλληλεγγύη φύση του Προβλήματος. Αλλά, αυτή τη φορά, το κάνουμε επίσης δημιουργώντας άλλα μέσα της κοινωνικής στρατηγίας, η οποία δημιουργεί τη στρατηγία του Προβλήματος. Αυτή η μορφή της Προβλήματος εφαρμόζεται εξιπιστωτική πραγματικότητα. Όπως εφαρμόζεται ήδη στο προηγούμενο μόδουλ, η πρόοδο του Προβλήματος σε αυτή τη στιγμή είναι μεταφέρει. Η φύση του Προβλήματος εφαρμόζεται από τις αισθήσεις και την προστατευτική προσέγγιση της ανθρώπισης, μέχρι τις εμπειρίες και την προστατευτική προσέγγιση των ανθρώπων. Σήμερα, συμβουλεύουμε να εμφανίζουμε την Προβλήματος. Προσέγγιζα την Προβλήματος ως δυναμική προσέγγιση και την αντιμετωπίσαμε όλες τις στιγμές της. Στην αρχή της Προβλήματος, όπου ελπίζουμε την Προβλήματος, στη στιγμή της εφαρμογής και της προστασίας, όπου εμφανίζουμε την Προβλήματος και η εμπειρία ξεκίνησε να εξελίξει, και επίσης, σε μια τελευταία στιγμή, όπου εμφανίζουμε τις εμπειρίες που είχαμε. Οι εμπειρίες είναι πάντα κεντρικές στην κοινωνία της Προβλήματος. Συμβουλεύει την πραγματική εμφανία της Προβλήματος και την ενδιαφέροντα της και της σχέσης. Ακριβώς, εμφανίζουμε τις εμπειρίες της Προβλήματος, αλλά πώς το κάνουμε? Προσφέροντας την εμπειρία της Προβλήματος, συμβουλεύουμε οι άνθρωποι, μη σχεδόν το σχέδιο. Προσφέροντας την εμπειρία μας, προσφέροντας άλλους να συμμετείχουν και να μοιραστούν το κοινό μας. Δεν προσφέρονταμε απλή εμφανία, στάτικη βιβλία ή σύμβουλ. Συμβουλεύουμε τη σχέση, συμμετοχώντας και εξελίξοντας όλες τις αισθήσεις. Η βιβλία, το πόνο, το ακούμα, το αίσθημα και το ήχο, τα άνθρωποι, το τραύμα και το σημαντικό. Τελικά, τι πραγματικά κάνουμε? Προσφέροντας και συμμετοχώντας μια ιστορία. Η συμμετοχή δεν συμβαίνει σε μια βαθμίδα. Προσφέροντας μια συμμετοχή εξελίξευση μπορεί να συμμετοχήσει την εμπειρία μας. Προσφέροντας μια ιστορία, συμμετοχούμε το κοινό της εμπειρίας μας, το συμμετοχούμε, το μιλήσουμε και το παρουσιάζουμε σε άλλους. Η συμμετοχή της εμπειρίας της πραγματικότητας και της συμμετοχής μπορεί να είναι είτε ένας συμμετοχικός εξελίξευσης, ή ένας γεγονός ή ακόμα και ένας γεγονός, εκείνος ή εσένα. Πραγματικά, όπως είπαμε σε προηγούμενες μότια, η συμμετοχή της συμμετοχής και η γεγονός, και ακόμα και η γεγονός, εκείνος ή εσένα, είναι πολύ δυνατή σε αυτήν την εποχή και καταφέρνει πολλές στήματα. Είναι οι συμμετοχοί, οι πραγματικοί και οι αξιολογικοί, οι δημιουργοί, οι μεδιωματικοί και, επίσης, οι πιστωτές, οι εξελίξευτες και οι εκπαίδευτες. Λοιπόν, σε αυτήν την εμπειρία της συμμετοχής της πραγματικότητας και της συμμετοχής της εμπειρίας της πραγματικότητας, πραγματικότητα και η εμπειρία της συμμετοχής της πραγματικότητας είναι σχετικά με το πώς οι άνθρωποι σχηματίζουν την πραγματικότητα και πώς η πραγματικότητα σχηματίζει τους ανθρώπους. Έτσι, η εμπειρία της συμμετοχής της πραγματικότητας και της εμπειρίας της συμμετοχής της πραγματικότητας είναι σχετικά με το πώς οι άνθρωποι σχηματίζουν την πραγματικότητα και πώς η πραγματικότητα σχηματίζει τους ανθρώπους. Έτσι, η εμπειρία της συμμετοχής της πραγματικότητας και της εμπειρίας της συμμετοχής της πραγματικότητας είναι σχετικά με το πώς οι άνθρωποι σχηματίζουν την πραγματικότητα και πώς η πραγματικότητα σχηματίζει τους ανθρώπους. Έτσι, η εμπειρία της συμμετοχής της πραγματικότητας και της εμπειρίας της συμμετοχής της πραγματικότητας είναι σχετικά με το πώς οι άνθρωποι σχηματίζουν την πραγματικότητα και πώς η πραγματικότητα σχηματίζει τους ανθρώπους. Έτσι, η εμπειρία της συμμετοχής της πραγματικότητας και της εμπειρίας της συμμετοχής της πραγματικότητας είναι σχετικά με το πώς οι άνθρωποι σχηματίζουν την πραγματικότητα και πώς η πραγματικότητα σχηματίζει τους ανθρώπους. Έτσι, η εμπειρία της συμμετοχής της πραγματικότητας και της εμπειρίας της συμμετοχής της πραγματικότητας είναι σχετικά με το πώς οι άνθρωποι σχηματίζουν την πραγματικότητα και πώς η πραγματικότητα σχηματίζει τους ανθρώπους. Έτσι, η εμπειρία της συμμετοχής της πραγματικότητας και της εμπειρίας της συμμετοχής της πραγματικότητας είναι σχετικά με το πώς οι άνθρωποι σχηματίζουν την πραγματικότητα και πώς η πραγματικότητα σχηματίζει τους ανθρώπους. Έτσι, η εμπειρία της συμμετοχής της πραγματικότητας και της εμπειρίας της συμμετοχής της πραγματικότητας είναι σχετικά με το πώς οι άνθρωποι σχηματίζουν την πραγματικότητα και πώς η πραγματικότητα σχηματίζει τους ανθρώπους. Έτσι, η εμπειρία της συμμετοχής της πραγματικότητας και της εμπειρίας της συμμετοχής της πραγματικότητας είναι σχετικά με το πώς οι άνθρωποι σχηματίζουν την πραγματικότητα και πώς η πραγματικότητα σχηματίζει τους ανθρώπους. Πρακτικά, όταν συμμετοχήσουμε μια εμπειρία μέσα από την ιστορία, το οποίο κάνουμε είναι ένας ανθρώπινος εξετάστασης που σχηματίζει τις μυαλές του ανθρώπου, σχηματίζει την αίσθηση και δημιουργεί συνδυασμούς, εφαρμόζει αισθήματα, συμμετοχήσει την πραγματικότητα και τις εμπειρήσεις, συμμετοχώντας με την ανοιχτή και την ενδυναμωμένη συμμετοχή που δημιουργεί μέσα από τη συμμετοχή, το οποίο, εν τέλος, ως επαφή και επίπεδο, προσέφερε να έχει μια εμπειρία και ενδυναμωμένη συμμετοχή μεταξύ της καινούργιας. Ή, σε άλλα λόγια, όταν συμμετοχήσουμε μια εμπειρία μέσα από την ιστορία, το οποίο κάνουμε είναι να εξετάσουμε. Εξετάσουμε το concept of framing in Module 10. When we frame, we develop the experience frame, where we link pragmatic and reality-based information and experience on the basis of interaction and in the logic of personal engagement without mediators. The experience frame works as a storyline and a cognitive device that provides meaning to an unfolding strip of events, experiences and occurrences, which are projected and communicated as important and further enables the engaged stakeholders to interconnect and to give meaning to social interactions. When we adopt the experience frame, we actually organize the information by applying the principles of choice and projection. This means that we select some certain aspects of a perceived reality and make them more silent in a communicating text and in our storytelling. This is to promote and to transfer the attention to a particular theme and its definition, causes, evaluation and proposed actions. Some techniques that we use while sharing our experiential story is for example the use of any kind of language, words, music, expressions. Moreover, we communicate not only the what but also how and why, so we incorporate all the fundamental questions of communication in our storyline. We address prospective concerns, make a point and provide information that facilitates putting things in perspective and broader context. Not only we keep our experiential storytelling anthropocentric, but further we layer the experience based on different levels of information and participation. We make the listening public part of the story. We get the public engaged and ask how can this impact travelers' experiences and transform the travelers' traditional identity of the impressions collector. We do not just list things, we narrate the experiential story and especially in today's digital era we actually do something more. We show this experience and personal engagement of our storytelling through social media networks. And because today's world is not only digital but also mobile, we make this interactive experiential story location aware using real world locations as added value. And remember, a location and a place is more than a landscape. It's the human testimonials, the personal, political, economic, cultural forces that shape the place and its people. So stories are everywhere and they are waiting to be heard, told, showed and shared. An experience is the special something that adds value dimension to the storytelling and gets it imprinted in the public's mind and is remembered. Worth noting is that the travel communicator or the traveler are not only looking for these experiences. Experiences are everywhere. A place and a community are limitless spaces where endless series of expressions may occur as Hellenic Tourism Organization felicitely promotes. But the travel communicator or the traveler are also longing to share these experiences with his or her friends. I am the stories I tell. The traveler is the whole of all his and her unique experiences of traveling life which he or she tells and shares. Moreover, these friends, the listening public to whom the experiences are communicated to, will dream also of these experiences and on top of that, they will also look for similar experiences. This is the impact of experiential storytelling. Let's see now an example of how plain experiences can be developed to stories and how stories can be developed to a sustainable travel storytelling with a plot. We take an example from Greece and the travel communication strategy of the Hellenic Tourism Organization. Step one is the digital space offered to the travelers in Greece to share publicly their experiences from their travels in Greece, composing the true Greece and hooking us to meet Greece. Step two are the audio-visual articulations that give voice to the experiences of the travelers in Greece through their testimonials, holding us to see you in Greece. Step three is the story about Greece, a mini-film with a story plot and a narrative visualization inviting us to see gods, myths and heroes everywhere we turn in Greece. So experiential storytelling tells you a story and triggers you to want to discover the place, the community and the people. It does make you want to dive into the story, to be able to live it with all your senses, to really experience it. It makes you part of the ecosystem and leads you to want to share it. It reveals the essence of all together, engaging everything, you, me, the place, the people, the community. A good example about this is the story about Crete, where the story reveals Crete as the island inside you, full of experiences waiting to be shown and shared. Experiential storytelling offers experiences that are created and not produced, that reveal personal engagement. It starts with an idea or theme that unfolds a story that leads to adventure, travel explorations and discoveries. This is the concept of the story. Then comes the location with its unique characteristics, nature, culture, society and the people. It is a location-based story now that leads the way to experience and it becomes an experience-scape now. After that, characters take place. The people that make the story and the experience come alive. The people that make the story and the experience come alive. Local community, engaged public, travelers, visitors, bypassers, locals. Add to all the former authenticity, creativity and interaction, the elements that cultivate synergy and communication, and then travel becomes experience and personal engagement, which act as key influences and facilitate the development of a sustainable travel story. Our creative task is entitled Be a Travel Communicator. Tell us travel stories from your personal travel experiences. Offer us a real-life testimonial with reliable information and experiences on a storyline and a narrative visualization. Communicate the travel experience of yours by sharing it with us and make us dream about the place or the community and the experience by describing it vividly. Hook us at your story theme, hold our interest in your story plot and pay us off by inspiring us, motivating us, educating us and also proposing an interaction. Select, emphasize and present, arrange the information in a plotline so that we can engage and interconnect to your story. Remember, everything should be reality-based storytelling of personal engagement, no fiction and no mediators. Our creative task number two is entitled Be a Travel Communicator but also Mediator and Educator. Find, track down and share with us travel reality-based experiential stories that you consider good practices and examples of sustainable travel storytelling. Explain us why you think it corresponds to a good example of taking public on an engaging journey. What does the story evoke and offer from the elements of the experience frame? How does it contribute to the creation of the authentic experiences repository and to the transition from the traditional identity of the traveler to the anthropocentric and social dimension of travel? This module, the module of Effective Communication Strategies in Travel, Experiential Storytelling, ends here and we will meet again online in our next module. Don't forget, our virtual discussion and dialogue continues on social media.